Editorial - Camacho Bercherlt, Mirna (Cooperativismo & Desarrollo, 2024)
With the purpose of disseminating the launch of the issue in question, some of the authors met in a seminar that aimed to elucidate the panorama of the SSE, as an object of research, based on the challenges and potential that it represents for the academic community. With this in mind, we were able to conclude that three of the most important challenges for SSE researchers are: 1) definition and delimitation of the concept, because it is broad and diverse, which can restrict the comparison and understanding of results obtained from research. This challenge is related to the legislation of each country, given that there are differences in the recognition and support of sse initiatives. 2) Evaluation of the impact of the organizations that make up the SSE, which is a challenge given that the conventional criteria for measuring success are not sufficient to capture all the social, cultural, and environmental benefits generated. 3) Education and connection, since there are few institutions that teach SSE and, in some programs, there are absences of topics in the specialized training of researchers, which limits the quality and quantity of research in this field and, added to this, is the scarce relationship between authors.
Keywords: Social and Solidarity Economy; Social Sciences; Research